2007
DOI: 10.1109/lpt.2007.902345
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Detection of Biochemical Agents Using Etched-Core Fiber Bragg Grating Sensors

Abstract: It is demonstrated that the etched-core fiber Bragg grating sensor can be used to detect down to a monolayer of biological and chemical agents immobilized on the surface of the fiber. Theoretical models based on calculating the effective index of the surrounding medium in the presence of immobilized layer(s) were developed and confirmed experimentally by immobilizing a monolayer of 3-aminopropyl-monoethoxydimethyl-silane (APMDS) and polymers of 3-aminopropyl-triethoxysilane (APTES) on the surface of the fiber.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…For example, some special fiber sensor designs, such as the exposed-core technique now being used in etched-core FBG sensors, were first realized by using polymer optical fibers. [62][63][64] Although most POFs have a higher refractive index than silica, a single-mode perfluorinated POF with a refractive index of 1.34 has been fabricated. 60 This low-index fiber has the potential for improvement in the performance of biosensors, because it results in a stronger optical coupling between a light signal and the surrounding biosensor analyte.…”
Section: Plastic Optical Fibersmentioning
confidence: 99%
“…For example, some special fiber sensor designs, such as the exposed-core technique now being used in etched-core FBG sensors, were first realized by using polymer optical fibers. [62][63][64] Although most POFs have a higher refractive index than silica, a single-mode perfluorinated POF with a refractive index of 1.34 has been fabricated. 60 This low-index fiber has the potential for improvement in the performance of biosensors, because it results in a stronger optical coupling between a light signal and the surrounding biosensor analyte.…”
Section: Plastic Optical Fibersmentioning
confidence: 99%
“…EFBGs have also been used for measuring molecular surface adsorption, though less widely, compared to their use for bulk refractometry [21], [22]. For example, Saini et al has demonstrated the detection of a monolayer of 3-aminopropyl-monoethoxydimethyl-silane and polymers of 3-aminopropyl-triethoxysilane on the surface of an EFBG [23]. For bulk index sensing, refractive index resolution of has been reported by Ladicicco et al [24] and a higher sensitivity sensor with an index resolution of has been reported by Athanasios et al [25], in which the fiber was etched down to 3.4 exposing the core to the surrounding medium.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] For these sensors, we completely removed the cladding and even part of the core of the fiber. We have demonstrated sensors with sensitivity to changes of the index of refraction of order 7 × 10 −7 .…”
Section: Introductionmentioning
confidence: 99%